#TITLE_ALTERNATIVE# - RIDWAN TRESNA NUGRAHA (NIM 10204001), AHMAD
Electronic structure of graphene and carbon nanotube (CNT), including energy dispersion relation and bandgap structure, can be obtained with such a simpler alternative method. Calculation is done by solving eigenvalues of Hamiltonian matrix in expansion of its basis functions. This method could be considered as a modication of tight-binding approximation. The same results found here compared with older calculation for graphene and CNT might be a reason of the method validity.